Evaluation of different changes in diurnal feed restriction for broilers (Research, Society and Development, 2021)
Feed restriction programs arose in the poultry industry as an alternative to improve zootechnical index rates. Thus, this study aimed to evaluate the effect of short-term feed restrictions on the performance of broilers. For this, 1,260 male were distributed in a completely randomized design in four feeding programs (FP), with nine replicates of 35 broilers each. The following FP were: P1 = ad libitum (AL); suspension of the daily feed supply, from 06:00 to 08:00 in the morning (RM) (P2), from 01:00 to 03:00 in the afternoon (RA) (P3) and P4 = 06:00 to 08:00, in the morning, and from 01:00 to 03:00, in the afternoon (RMA). There was no statistical difference in body weight at 21, 35, and 42 days, feed intake, feed conversion, carcass characteristics, physical measurements, femur and tibia fracture resistance, and the femur Seedor index. The weight gain in the RMA group was higher in two evaluation periods (35 and 42 d) in comparison with the AL group. The glycemic index was lower in broilers subjected to feed restriction than in those subjected to AL. The RA reduced the weight of abdominal fat and feathers. The tibia Seedor index in the AL group was lower than those in the RA and RMA groups. The quantitative feed restriction program for 4 hours improves performance and bone and economic quality in broilers, from 8 to 42 days old.